Regionalism, literature and three Peruvian novels of the 19th century - Noriega Bernuy, Julio (1986)
Regionalism, underestimated by many and valued in its real dimension by few people, is still today a matter that requires full clarification. Reduced to a localism, ruralism or landscaping in some, framed in the geographical and economic for others, the regionalist phenomenon in Peru has been postponed in the literary. The following pages attempt to make up for this oversight and, perhaps, unravel the true sense and meaning of regionalism in the cultural field. With this purpose, the thorny question of the region and regionalism in Peru is analyzed, its repercussion in the national literature in general and in three fundamental novels of the 19th century, in particular.